Effective Content Organization Of A Portal - Levy, Moria (Journal of Knowledge Management Practice, 2009)
Portals are very commonly used platforms that address many needs. This paper provides a unique method of organizing portal pages and therefore enabling accessibility of the information and knowledge provided in the portal. The portal is the main platform for knowledge management solutions and for content rich applications; accessibility has been found to be a critical factor for portal use and business success. The method reported is based on organization by context rather than by knowledge format. Relating the context to processes of work and main users' needs, as defined by field users, yields high-level portal usability and therefore to effectively built portals.
Keywords: Knowledge management; Portal; Content organization